Applied architecture patterns on the Microsoft platform : an in-depth, scenario-driven approach to architecting systems using Microsoft technologies - Seroter, Richard; Ashkenazi, Ofer (Packt Pub., 2010)
An in-depth scenario-driven approach to architecting systems using Microsoft technologies with this book and eBook.
Keywords: SQL server.; Microsoft BizTalk server.; Microsoft .NET Framework.; Microsoft BizTalk server; SQL server; Microsoft .NET Framework; Client/server computing.; Computer programming.; elektronické knihy; electronic books